An updated view of the oligosaccharyltransferase complex in Plasmodium. (26th March 2019) - Tamana, Stella; Promponas, Vasilis J
Abstract: Despite the controversy regarding the importance of protein N-linked glycosylation in species of the genus Plasmodium, genes potentially encoding core subunits of the oligosaccharyltransferase (OST) complex have already been characterized in completely sequenced genomes of malaria parasites. Nevertheless, the currently established notion is that only four out of eight subunits of the OST complex—which is considered conserved across eukaryotes—are present in Plasmodium species. In this study, we carefully conduct computational analysis to provide unequivocal evidence that all components of the OST complex, with the exception of Swp1/Ribophorin II, can be reliably identified within completely sequenced plasmodial genomes. In fact, most of the subunits currently considered as absent from Plasmodium refer to uncharacterized protein sequences already existing in sequence databases. Interestingly, the main reason why the unusually short Ost4 subunit (36 residues long in yeast) has not been identified so far in plasmodia (and possibly other species) is the failure of gene-prediction pipelines to detect such a short coding sequence. We further identify elusive OST subunits in select protist species with completely sequenced genomes. Thus, our work highlights the necessity of a systematic approach towards the characterization of OST subunits across eukaryotes. This is necessary both for obtaining a concrete picture of the evolution of the OST complex but also for elucidating its possible role in eukaryotic pathogens.